Studi Pengikatan Cadmium (II) pada Resin Anorganik Titanium Oksida dan Zirkonium Oksida - Sunarhadijoso Soenarjo; Titiek Martati; Murti Winanti; Atmi Wirasti (JURNAL ILMU KEFARMASIAN INDONESIA, 2005)
Immobilization of Cd-(II) in production technology of indium medical radioisotopes (lll In or 115min) by means of 112Cd (p, 2n) 11 In or 114Cd (n,y) 115Cd 115mIn nuclear reaction is an important step regarding to the quality of the produced radioactive indium and efficiency of the utilization of the enriched targets (112Cd or 114Cd). The phenomena and capacity of Cd-(II) immobilization were studied using two kinds of inorganic oxide resins, i.e. titanium oxide and zirconium oxide. The aim of this study is gaining experimental data supporting the utilization of the resins in the production of 111In and 115min. The immobilization of Cd-(II) was proceeded by treating standard solutions of Cd-(II) with the resins followed by measurement of Cd-(II) content of the treated solution before and after treatment. The separation of the treated Cd-(II) solution from the resin was performed by means of centrifugation, while the measurement of Cd-(II) was performed by means of Ultra Violet spectrophotometry. The ready-used titanium oxide from Merck did not bind Cd-(II) even after being treated with several kinds of activating media. Zirconium oxide synthesized from the reaction of ZrOCI,. 8H,O with a basic solution of NaOH was in the form of the hydrate compound formulated as ZrO. nH,O with the value of n=(1.7034 +0.0186) and showed a capability to bind Cd-(II) higher than that of zirconium oxide synthesized with a basic solution of NH,OH or of the ready-used ZrO2. In general the Cd-(II)-binding capacity of Zro, tends to decrease with increasing of the amount of Zro.